Voices from the Mississippi Hill Country : The Benton County Civil Rights Movement - DeBerry, Roy; Lyons, John, 1981-; Klein, Stephen, 1936-; Futorian, Aviva (Book collections on Project MUSE., 2020)
"An in-depth oral and hyperlocal history of a rural county and its fight for civil rights"--